Liberalism - Von Mises, Ludwig, 1881-1973 (Book collections on Project MUSE., 2005)
"This book presents the theoretical and practical arguments for liberalism. Mises contrasts liberalism with other conceivable systems of social organization such as socialism, communism, and fascism. He is also more specific here than elsewhere in applying the liberal program to economic policy, domestic and foreign."--Jacket